Local Wisdom Used Wildlife Behavior as Indicators of Natural Phenomenon in Maluku Small Islands - Imanuel Kaya; Ernywati Badaruddin; Ivonne R G Kaya (Tropical Small Island Agriculture Management, 2022)
The people of Maluku, since their ancestors, have been known as a society with various social institutions which are, in fact, very appreciative of the living and non-biological natural resources around them. It has caused some historians to argue that the Maluku people are religious people oriented toward the nature surrounding their lives. The various forms of "traditional local wisdom" that are owned and still applied to this modern century have no difference. They are even more adhered to by the community regarding the conservation of living natural resources and their ecosystems. Meanwhile, the government enforces various laws and regulations but is not adequately socialized to society. In the future, challenges (Hotu mese) are already a philosophy of the Maluku people. They use it as a "Nanaku" (experience) to serve as an indicator to recognize natural phenomena and use it for their resilience to conquer the surrounding nature. This research was conducted to know the various forms of local wisdom of traditional communities in Maluku that have beneficial values for human life. The expected output of the research was that scientists can be motivated to conduct research to "answer scientific truth" to the forms of local wisdom of traditional communities, which are often judged as "sacred", "archaic", or "superstitious" for today's modern society. The Maluku people who inhabit small islands have integrated with their limited natural life. This limitation causes them to utilize all available components of living natural resources and ecosystems to fulfil their daily needs. The results showed that the local wisdom of the Maluku people can still be used to meet the needs of ecologists and the general public in carrying out activities in the wild, both in the forest and at sea, so as not to experience unwanted things.